Improving Regional Language Comprehension among Eighth-Grade Students at Telkom Junior High School Makassar - Abdul Rauuf Muri; Sumarlin Rengko HR; Muhlis Hadrawi; Pammuda; Mutahharah Nemin Kaharuddin; Mirza Kamal Pahlevi; Widya Vitaloka (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to improve students’ understanding of the Makassar local language among eighth-grade students at SMP Telkom Makassar. The research employed a quantitative approach using a quasi-experimental one-group pretest–posttest design. The participants consisted of seven Grade VIII classes involving 183 students. The research instrument was a multiple-choice test administered before and after the instructional intervention. Data were analyzed descriptively and using normalized gain (g) based on Hake’s formula. The results show that the average pre-test scores ranged from 35.58 to 43.27 and increased to 62.24–83.52 in the post-test. The g-Hake analysis indicates that six classes achieved a medium improvement category (g = 0.342–0.557), while one class reached a high category (g = 0.734), with an overall weighted g of 0.513. These findings indicate that Makassar language instruction is effective in improving students’ understanding and has potential to strengthen linguistic competence and preserve local culture in schools.